Case Report: From coma to genetic insights: identification of a novel pathogenic variant in Chinese neonatal CTLN1 - Deng, Lijing; Liu, Yaping; Chen, Kai; Qiu, Jianwu; Chang, Lu; Xia, Junxia; Wang, Yanrong (Frontiers in Pediatrics, 2025)
Citrullinemia type I (CTLN1) is an autosomal recessive disorder caused by variants in the arginine succinate synthase gene (ASS1). These variants result in arginine succinate synthase deficiency, leading to a disruption of the urea cycle and hyperammonemia. To date, only a handful of CTLN1 cases have been reported in China. One neonate responded poorly 30 h after birth and progressed to coma several hours later. Family history revealed that the neonate's older brother had also died a few days after birth. Biochemical tests on admission confirmed hyperammonemia and elevated levels of citrulline and urinary orotic acid-3. Genetic analysis revealed that the parents were carriers of two heterozygous variants in ASS1, c.910C>T(p.Arg304Trp) and c.839-1G>A, respectively. However, the splice site variant c.839-1G>A was not present in the control databases. Minigene analysis of the c.839-1G>A resulted in the product of r.839del [p.(Gly280Valfs*15)]. In conclusion, we have identified a case of CTLN1 and diagnosed a novel pathogenic variant in the ASS1 gene, c.839-1G>A, expanding the variant spectrum of ASS1. Currently, there are few reports of CTLN1 cases featuring such severe clinical manifestations and an onset at such a young age.